1979
DOI: 10.1103/physrevlett.42.1321
|View full text |Cite
|
Sign up to set email alerts
|

Angular Dependence of Proton Polarization in the Reactionγdpnand a Partial-Wave Analysis of Possible Dibaryon Resonances

Abstract: The angular dependence of proton polarization in yd--pn has been measured at photon energies between 400 and 650 MeV. The polarization and differential-cross-section data are consistently explained by introducing a dibaryon resonance I{J P ) = 0(3 + ) or 0(1 + ) at « 2360 MeV.In our previous experiment, 1 we measured the proton polarization in the reaction yd-pn at # c#m , = 90° at laboratory photon energies E y = 350-700 MeV. Unexpectedly large polarization was found atE y = 550 MeV, and this feature was conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…In fact, such an effect has already been looked for previously by Kamae et al in corresponding data from the Tokyo electron synchrotron [129,130,131,132]. In order to describe the observed large polarizations in the region of d * (2380), they fitted a number of resonances to the data, among others also a J P = 3 + state.…”
Section: Electromagnetic Excitation Of D * (2380)mentioning
confidence: 86%
See 2 more Smart Citations
“…In fact, such an effect has already been looked for previously by Kamae et al in corresponding data from the Tokyo electron synchrotron [129,130,131,132]. In order to describe the observed large polarizations in the region of d * (2380), they fitted a number of resonances to the data, among others also a J P = 3 + state.…”
Section: Electromagnetic Excitation Of D * (2380)mentioning
confidence: 86%
“…Actually groups at Tokyo had been quite close already as early as 1977 considering measurements of the proton polarization in deuteron photodisintegration γd → pn [129,130,131,132]. They observed a strong increase of the polarization at energies beyond √ s = 2.2 GeV, reaching a maximum around 2.38 GeV and decreasing thereafter.…”
Section: Former Occasions For Its Discoverymentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the maximal resonance effect is expected to be at a scattering angle of Θ = 90 • . In fact, such an effect has already been looked for previously by Kamae et al in corresponding data from the Tokyo electron synchrotron [26,27]. In order to describe the observed large polarisations in the region of d * (2380) they fitted a number of resonances to the data, among others also a J P = 3 + state.…”
Section: * (2380) Photoproductionmentioning
confidence: 84%
“…The possibility exists not only to extract the d * (2380) photo-coupling per se, but also to get hints about the d * (2380) electromagnetic properties, such as its electric quadrupole moment, its magnetic octupole moment, etc. Indeed, the first irregularities in deuteron photodisintegration were observed in the 1970s in proton polarization measurements d(γ, p)n [17,18]. It was suggested that the high proton polarization (P p ∼ 100%) observed at E γ ≈ 570 MeV might originate from a yet unknown six-quark particle with mass ∼ 2380 MeV and quantum numbers I(J P ) = 0(3 + ), consistent with the d * (2380) later found in nucleon-nucleon scattering experiments.…”
Section: Introductionmentioning
confidence: 99%